Office shock creating better futures for working and living - Johansen, Robert (Oakland Berrett-Koehler Publishers, 2023)
Leading futurist Bob Johansen and workplace architect Joseph Press guide organizations and individuals on how to weather the inevitable future of "office shocks." Most people have experienced "office shock" during the past two years, with the pandemic disrupting where and how they work. It's clear that we can't go back to the office the way it was. This book reimagines the office and shows how we can plan for more sustainable ways of working. Instead of just focusing on the present moment, Office Shock includes a FutureBack perspective, which refers to thinking back from the future and allows us to anticipate directions of change. The book starts by exploring the history of the office and then looks to the future to navigate office shock. It identifies key spectrums of choices, including purpose and desired outcomes, for better office futures and offers FutureBack recommendations for individuals, organizations, and policy makers. The book ends with a series of possible action steps we can all take together. We're in a decisive decade, and this book offers a way forward that is based on adaptability and agility"
Includes bibliographical references and index.
Keywords: Office management--Social aspects